The politics of water in Africa : norms, environmental regions and transboundary cooperation in the Orange-Senuqu and Nile Rivers - Jacobs, Inga M. (London ; New York : Continuum, 2012)
Water resources and related issues are of great significance in 21st century politics. In Africa, for example, hydropolitics affect politics and policymaking at the local, national, and international levels. To investigate water politics, this unique work focuses on the issue transboundary water governance in Southern and Eastern Africa. Based on extensive field research, it offers a comparative study of the Orange Senqu and Nile basins in Africa, arguing that both causal and behavioral factors (such as localization and trust building) drive the multi-leveled development of cooperative management norms and foster the creation of regional communities of interest. The book combines theory, analysis, and fieldwork within the framework of Constructivism as well as a wide range of examples to identify and analyze the nature of norms in hydropolitics. By doing so, it will help shape the debate on how water conflict and cooperative governance should evolve and will interest anyone studying African politics, hydropolitics, and issues of development--
Introduction--1. Constructing Complexity and Soft Power in Transboundary Water Governance--2. Multi-level Water Governance: Factors, Actors, Process--3. The Orange-Senqu River Basin and the Importance of the Past--4. The Nile River Basin and a Changing Landscape--5. Comparison of Multi-level Water Governance in Southern and East Africa--6. Scaling out to Environmental Politics: Lessons learned from Water--7. Water as a tool for Regional Integration and Policy Implications--Conclusion. Exploring New Frontiers in Transboundary Water Governance.
Includes bibliographical references (p. [211]-235) index.
Keywords: Water-supply -- Political aspects -- Africa -- International cooperation -- Case studies; Water-supply -- Government policy -- Africa -- International cooperation -- Case studies; Water-supply -- Political aspects -- Orange River Watershed -- International cooperation; Water-supply -- Political aspects -- Nile River Watershed -- International cooperation; Water-supply -- Government policy -- Orange River Watershed -- International cooperation